An analytical study of severe floods of July 1978 in Bagmati and Adhwara group of rivers (MAUSAM, 1981)
Synoptic and hydrometeoro1ogical aspects of severe floods that visited the Bagmati and the Adhwara group of rivers in north Bihar in July 1978 have been studied in this paper. The floods touched or surpassed the highest flood levels of 1975 in the two rivers, inspite of much less total storm precipitation yield and less favourable antecedent precipitation conditions. This phenomenon has been explained with the help of short duration intensity of the storm rainfall.